(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Nowadays it is necessary to define actual global research trends in disciplines in order to determine the major research topics, discoveries and global scientific networks. The goal of the work was to determine the main topics and research trends in agricultural engineering. For this caser he method of modified bibliometric analysis was applied. Such analysis of the keywords frequency occurrence and the links between the keywords in Biosystems Engineering Journal shows that in the three analysed periods, certain keywords invariably remain dominant. These are “model”, “system” or “systems”, “temperature” and “water”. The highest number of publications was qualified for the CIGR section: Information Technology. It can be, therefore, stated that in the recent period the most intensively developing researches were dedicated to the application of IT tools in creation various types of models, allowing to simulate and optimize agricultural processes. A majority of publications covered decision-making support (Decision Support Systems), image analysis application, and automation of agricultural processes.